2022
DOI: 10.1111/jcmm.17318
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 alleviates pulmonary hypertension by inhibiting mTORC1/EIF4EBP1 pathway via H19

Abstract: Pulmonary hypertension (PH) is characterized by progressive vasoconstriction and pulmonary artery remodelling. 1 Uncontrolled expansion of pulmonary artery smooth muscle cells (PASMCs), pulmonary vascular endothelium damage and excessive extracellular matrix deposition are the common pathological hallmarks of PH. 2 Despite the availability of treatments that provide symptomatic relief, till date, there has been no effective treatment for PH. Thus, there is still an urgent need to find possible regulatory targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Different blood samples, different models, tissues and cell samples may have caused some discrepancies. 33 H19 with a primary structure up to 2.3 KB can act as a ceRNA to adsorb miRNA, thereby weakening its interference with the targeted mRNA. 29,34 Our ndings imply that H19 sponges let-7 g, which is consistent with a prior publication.…”
Section: Discussionmentioning
confidence: 99%
“…Different blood samples, different models, tissues and cell samples may have caused some discrepancies. 33 H19 with a primary structure up to 2.3 KB can act as a ceRNA to adsorb miRNA, thereby weakening its interference with the targeted mRNA. 29,34 Our ndings imply that H19 sponges let-7 g, which is consistent with a prior publication.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study indicated that knockdown of H19 significantly promoted the proliferation of rPASMCs, which seems to contradict our finding. Different blood samples, different models, tissues and cell samples may have caused some discrepancies [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Damgaard RB's study revealed that OTULIN-de cient livers with steatohepatitis exhibit aberrant mTOR activation 18 . Additionally, FGF21 functions as an inhibitor of mTORC1 to regulate hepatic insulin action and maintain glucose homeostasis 19 . Li et al utilized complementary genetic models with gain or loss of function of mTOR signaling in the liver and demonstrated the bene cial effect of mTOR in liver IR injury 20 .…”
Section: Discussionmentioning
confidence: 99%